Dysexecutive functioning in ALS patients and its clinical implications. Issue 3 (June 2015) - Kasper, Elisabeth; Schuster, Christina; Machts, Judith; Bittner, Daniel; Vielhaber, Stefan; Benecke, Reiner; Teipel, Stefan; Prudlo, Johannes
Abstract Pronounced cognitive and behavioural impairments in amyotrophic lateral sclerosis (ALS) concern executive functions and executive behaviour. The valid measurement is challenging as motor disabilities may mask everyday functioning. The aim of this study was to determine a detailed characteristic pattern of executive impairment in ALS in order to effectively interpret their clinical impact. We investigated 98 ALS patients without or with frontotemporal dementia (FTD), and 70 healthy controls using a comprehensive neuropsychological test battery focusing on executive functions and executive behaviour. We analysed the impairment of executive functions and their clinical significance for patients' daily routines. Results demonstrated that around 70% of cognitively impaired ALS patients without FTD showed disturbances in executive functioning. Behavioural abnormalities primarily manifested in symptoms of apathy. Patients without FTD were most impaired in the executive domain regarding initiation and shifting; this contrasted their almost preserved processes relating to updating, inhibition, and complex problem solving. ALS-FTD patients showed deficits in all analysed processes. Our study suggests that executive dysfunctioning in cognitively impaired ALS patients without FTD does not preferentially affect the more complex regulatory processes. These findings indicate potential mechanisms for ALS patients to compensate for executive dysfunction in daily routine.